Pengaruh kebijakan dividen, keputusan investasi, dan keputusan pendanaan terhadap nilai perusahaan manufaktur di masa pandemi Covid-19 - Diwi, Amartya; Sucahyo, Usil Sis (Universitas Widya Mataram, 2024)
The pandemic period has had an impact on companies, such as a decrease in stock prices and financial performance, which can affect the value of a company. The value of a company is a condition where public trust becomes an indicator of the company's achievements, from the time it was established until the present. This research was conducted to analyze the three variables related to finance, namely dividend policy, investment decisions, and financing decisions, in relation to the value of a company, which yielded inconsistent results. The sample used consisted of 53 companies selected based on which companies included the variables under study. The analytical technique used was multiple linear regression analysis, which concluded that the value of the company is positively and significantly influenced by dividend policy, while investment decisions and financing decisions do not have a significant impact on the value of the company.